Republic of Tajikistan : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Waiver of Nonobservance of a Performance Criterion and Request for Modification of a Performance Criterion-Staff Report; Staff Supplements; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Economic activity is on the upswing in Tajikistan, bolstered by higher hydroelectric power production. The government is working to address the structural energy deficit and achieve energy independence, raise social expenditures, maintain a flexible exchange rate regime, and continue structural reforms. Medium-term fiscal consolidation will be essential while striking a careful balance between social and capital spending. Macroeconomic policies should shift from an anti-crisis to a post-crisis footing. Follow-through on structural reforms is essential both for continued donor support and for meeting medium-term macroeconomic objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet